2020
DOI: 10.1021/acsinfecdis.9b00385
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cisplatin and Palladium(II) Complexes as Potent Metallo-β-lactamase Inhibitors for Targeting Carbapenem-Resistant Enterobacteriaceae

Abstract: The emergence and prevalence of carbapenem-resistant bacterial infection have seriously threatened the clinical use of almost all β-lactam antibacterials. The development of effective metallo-β-lactamase (MβL) inhibitors to restore the existing antibiotics efficacy is an ideal alternative. Although several types of serine-β-lactamase inhibitors have been successfully developed and used in clinical settings, MβL inhibitors are not clinically available to date. Herein, we identified that cisplatin and Pd(II) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…5 a), suggesting the inactivation rate follows pseudo-first-order rate kinetics. These results imply that the hydroxamate may covalently bind to the target [38] . The K obs (observed rate constant) were fitted against inhibitor concentration by nonlinear regression to calculate K I (the concentration of inacti-vator at the half-maximum inactivation rate constant), k inact , and k inact /K I values, which are 1.18±0.43 µM, 0.0075±0.0005 s −1 , and 6.4x10 3 M −1 s −1 , respectively [37] .…”
Section: Inhibition Mode Assaymentioning
confidence: 85%
See 2 more Smart Citations
“…5 a), suggesting the inactivation rate follows pseudo-first-order rate kinetics. These results imply that the hydroxamate may covalently bind to the target [38] . The K obs (observed rate constant) were fitted against inhibitor concentration by nonlinear regression to calculate K I (the concentration of inacti-vator at the half-maximum inactivation rate constant), k inact , and k inact /K I values, which are 1.18±0.43 µM, 0.0075±0.0005 s −1 , and 6.4x10 3 M −1 s −1 , respectively [37] .…”
Section: Inhibition Mode Assaymentioning
confidence: 85%
“…To further study the inhibition mode of the hydroxamates and thiosemicarbazones on M pro , 1a and 2b were chosen to determine the enzyme kinetic parameters [37] , [38] , [39] . The above assay reveals that 1a inhibit M pro in a time-dependent pattern, and the kinetic progression curves exhibited a biphasic character ( Fig.…”
Section: Inhibition Mode Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…During our investigations of transition metal drugs and metal complexes for new inhibitors of NDM-1 and other MBLs, Chen and colleagues identified cisplatin and Pd complexes as potent inhibitors of MBL activity [ 49 ]. From their data, they posit that the metal or ligand-bound metal species replaces one of the zinc ions in the active site.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Chen Cheng et al found that disulfiram is a promising candidate for the development of NDM-1 inhibitors, which can covalently bind to NDM-1 by forming an S–S bond with Cys208 residue at the active site ( Chen et al, 2020b ). At the same time, some metal complexes (cisplatin and Palladium(II) complexes) ( Chen et al, 2020a ) and DNA aptamers ( Khan et al, 2019 ) have also been found to have inhibitory effects on NDM-1. Among them, the metal complexes inhibited MβLs through a new inhibition mode, which binds to the Cys208 residue in the active site, causing Zn 2+ to be replaced by other ions.…”
Section: Introductionmentioning
confidence: 99%